Growth Performance and Realized Heritability in a Mass-Selected Strain of Silver Pomfret (Pampus argenteus) - Chunlai Qin; Chang Li; Jie Tang; Xiang Huang; Yuanbo Li; Jiabao Hu; Yajun Wang (Animals)
In China, the silver pomfret (Pampus argenteus) is one of the most popular marine edible fish. To analyze the genetic characteristics of P. argenteus across three generations and evaluate whether continued progress can be made in body weight and growth traits, growth traits of the third-generation P. argenteus breeding and control groups were measured at 60, 90, and 120 days post-hatch. Using Pearson correlation and path analysis, we found a strong correlation between the growth characteristics of the third-generation P. argenteus and its body weight, with fork length and body length showing the strongest associations. Body weight, body length, and fork length all showed high levels of realized heritability at 120 days, with respective values of 0.55, 0.57, and 0.56. The genetic gain for body weight in the breeding groups over the three periods was 29.70 ± 0.58% (2.43 ± 1.17 g), which was significantly higher than the genetic gain for body length (8.90 ± 3.91%, 0.56 ± 0.29 cm) and fork length (8.08 ± 3.69%, 0.57 ± 0.33 cm). At harvest on day 120, the breeding group was 33.93% greater than the control group in terms of body weight. These results indicated that through mass selection, improvements were made to body weight of P. argenteus, leading to an enhancement in its growth performance. In the meantime, there was roughly equal genetic gain for body length, body weight, and fork length. These experiments showed that mass selection can effectively increase P. argenteus body weight, which will improve the species’ growth performance. These findings suggest that substantial genetic improvements can be achieved through mass selection for body weight, providing strong support for the ongoing P. argenteus selective breeding program.